UMA ANÁLISE SOCIOLÓGICA DA FORMAÇÃO DE LIDERANÇA ENTRE OS ESTUDANTES NA EDUCAÇÃO BÁSICA - Bandeira, Rose Mary Beserra Pinto (2012)
The two key themes of the Education Sociology are the formation of social groups inside of classroom and leadership groups within the classroom universe. Several academic works consider the role of the teacher because it is actually nominated institutional leadership. In this research we tried to approach the student leadership building up as a subject of equal importance as the role of the teacher. We analyzed the position of the school entity towards student leadership issues within the education process. To complete our investigation, of qualitative nature, we searched bibliography associated to the subject and we selected several authors as basic references as well as school documentation like: statutes, political pedagogical projects and internal procedures, interviews, classroom observation and associated analyses, etc. According to some people responsible for the education of students basically two types of leadership can be selected: one negative and another positive. The investigations of this work indicated that the education institutions also strongly contribute together with the dominate ideology forces to select for either the senior or junior levels of society leadership.